2021
DOI: 10.1021/acsmaterialslett.1c00327
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Materials for Perovskite Solar Cells with Enhanced Efficiency and Stability

Abstract: With outstanding photovoltaic properties, metal halide perovskite materials have marked great achievements in the field of next-generation solar cells; however, there still remain some challenges that hinder the commercialization progress regarding device efficiency and stability. Introducing novel materials with enhanced properties in perovskite solar cells (PSCs) is a promising strategy to overcome these difficulties. Two-dimensional materials (e.g., graphene and its derivatives, transition-metal dichalcogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 113 publications
0
15
0
Order By: Relevance
“…Recently, Hui et al reported ionic liquid MAFa (Table 5) as a solvent for fabrication of stable blackphase α-FAPbI 3 at room temperature and high humidity (Figure 8g−8i). 132 1 H NMR and 13 C NMR spectra demonstrated that the solvent MAFa has strong interactions with PbI 2 through C = O•••Pb chelation and N−H•••I hydrogen bonds, which promote the vertically aligned growth of PbI 2 thin films with respect to the substrate and prevent the transformation of PbI 2 to δ-phase perovskite (Figure 8g). The vertically grown structure has nanometer-scale ion channels between the layered PbI 2 that facilitate the permeation of FAI into the PbI 2 films and direct reaction, transforming into α-FAPbI 3 after the deposition of FAI even without annealing (Figure 8h).…”
Section: ■ Properties Of Typical Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hui et al reported ionic liquid MAFa (Table 5) as a solvent for fabrication of stable blackphase α-FAPbI 3 at room temperature and high humidity (Figure 8g−8i). 132 1 H NMR and 13 C NMR spectra demonstrated that the solvent MAFa has strong interactions with PbI 2 through C = O•••Pb chelation and N−H•••I hydrogen bonds, which promote the vertically aligned growth of PbI 2 thin films with respect to the substrate and prevent the transformation of PbI 2 to δ-phase perovskite (Figure 8g). The vertically grown structure has nanometer-scale ion channels between the layered PbI 2 that facilitate the permeation of FAI into the PbI 2 films and direct reaction, transforming into α-FAPbI 3 after the deposition of FAI even without annealing (Figure 8h).…”
Section: ■ Properties Of Typical Ionic Liquidsmentioning
confidence: 99%
“…As the third-generation photovoltaic cells, perovskite solar cells (PSCs) have attracted enormous attention and shown fast development in both academia and industry, which are attributed to the low-cost solution processing of devices and remarkable optoelectronic properties of metal halide perovskites, including tunable bandgap, high absorption coefficient, excellent charge mobility, and long photocarrier diffusion length. Benefitting from composition, solvent, , surface, and interface engineering, as well as development of novel charge-transporting materials for PSCs, the power conversion efficiency (PCE) of single-junction PSCs dramatically progressed from 3.81% to 25.7% to date, the highest value obtained for polycrystalline solar cells.…”
mentioning
confidence: 99%
“…2D materials (TDMs) are promising functional materials to modify the perovskites due to their excellent thermal, mechanical, electrical, and optical properties, which are used as electrodes, carrier transporting layers, buffer layers, and perovskite additives. [12][13][14][15][16] Among the numerous TDMs, graphitic carbon nitride (g-C 3 N 4 ) is a versatile TDM with a similar structure to graphene, which has been widely used in applications of medical science, energy storage, supercapacitors, and catalysis. [17][18][19][20][21] However, the investigation of g-C 3 N 4 in the field of PSCs seems to be still in its infancy, [22][23][24] compared with other research hotspots.…”
Section: Introductionmentioning
confidence: 99%
“…However, the limited operational-stability of PSCs presents a significant hurdle in the path toward their commercialization, [7] although steady progress is being made in addressing this shortcoming. [8][9][10] PSCs' instability arises from the rapid degradation of MHPs under elevated temperatures (≈150 °C) or/ and exposure to moisture, oxygen, and UV light.…”
Section: Introductionmentioning
confidence: 99%